Narrative structure of Boris Zhytkov’s novel “Viktor Vavich” - Vlasov, Daniil (Visnyk Kharkivsʹkoho nat͡s︡ionalʹnoho universytetu im. V.N. Karazina. Serii͡a︡ filolohii͡a, 2023)
The purpose of this article is to analyze the narrative structure of B. Zhytkov's novel «Viktor Vavіch» (1926-1931, published in 1999). The relevance of the study is due to the fact that narratological analysis is a promising area of modern philological science, but the narrative characteristics of B. Zhytkov's novel are almost never revealed in literary studies of the text. The author proposes to use the model of communicative instances and points of view of W. Schmid, to clarify the relationship between the narrative structure and the novel's problems, narrative factors of characterization, etc. It is proved that the novel is based on a complex polyperceptual composition, in which the narrator's colorful figure is almost not revealed, who remains as if outside the text, allowing his characters to present their worldview almost independently. The author examines the figure of the titular character Viktor Vavich and how his image is constructed by narrative means. It is proved that the structure of consciousness represented by Viktor Vavich is dual and incorporates both the hero's own consciousness and the imaginary image of the external other constructed by him, which subjects him to critical evaluation. This duality of self-perception is characteristic of several characters in the text, but only in the case of Vavich does it become a psychological dominant that ultimately destroys his personality and leads him to decline and death. It has been shown that despite the polyperceptual composition and the unidentified narrator, there is a monologic organizing principle in the text, which is manifested through the functioning of a rather uniform and stable motivic system that is realized through different perceptual instances. In this way, the text forms an imaginary dialogue between two instances: a monological intention that exists in the categories of its own ideology and a polyphony of consciousnesses that do not have a colored narrator figure to give them any ideological assessment.